Custom synthesis of molecular imprinted polymers for biotechnological application: preparation of a polymer selective for tylosin - Piletsky, Sergey A.; Piletska, Elena V.; Karim, Kal; Foster, Graham; Legge, Colton; Turner, Anthony P. F. (Elsevier, 2004)
A molecularly imprinted polymer (MIP) selective for tylosin was designed and synthesised using a computational method (MIP “dialling”). In re-binding experiments the MIP demonstrated high affinity for tylosin in aqueous solutions and in organic solvents. The synthesised polymer was tested for re-binding with the template and related metabolites such as tylactone, narbomycin and picromycin. The HPLC analysis showed that the computationally designed polymer is specific and capable of separating the template from its structural analogues. The MIP was capable of recovering tylosin from broth samples. The polymer capacity for tylosin was estimated as 6.4 mg/g for MIP, which was suitable for practical application and tylosin recovery from broth samples. Among the advantages of this was the possibility to adsorb tylosin from a complex media with easy removal of oils and other impurities which are present in significant quantities, which can create problems for its chromatographic purification procedure. The MIP “dialling” procedure can have a general significance for the fast preparation of specific adsorbents for biotechnological appli
Keywords: Computational design